Numerical Solution of Linear System of Fredholm Integral Equations Using Haar Wavelet Method (Journal of the College of Basic Education, 2023)
The aim of this paper is to present the numerical method for solving linear system of Fredholm integral equations, based on the Haar wavelet approach. Many test problems, for which the exact solution is known, are considered.Compare the results of suggested method with the results of another method (Trapezoidal method). Algorithm and program is written by Matlab vergion 7.Keywords: linear system of Fredholm integral equations, Haar wavelet metho